Inhibition of Escherichia coli Induced Bacterial Meningitis by Ansamycin Loaded Polymeric Nanoparticles - Wang, Li; Pan, Feng; Geng, Jun (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: Bacterial meningitis is a serious medical disorder that should be treated as soon as possible. Aim: The effect of ansamycin as a nanoformulation on Escherichia coliinduced meningitis was investigated. Materials and Methods: By injecting Escherichia coli directly into the brains of Swiss Albino mice, an experimental meningitis model was established. Results: As expected, TNF-α, IL-6, and IL-10 secretion was stimulated, following neutrophil infiltration. Additionally, the BBB’s vasopermeability was raised. Ansamcyin nanoparticles were delivered to assess their therapeutic potential in preventing bacterial meningitis caused by Escherichia coli. Ansamycin nanoparticle-treated mice produced less tumour necrosis factor alpha and interleukins when brain tissue was stained, compared to nontreated mice. E. coli-induced increases in the permeability of the blood-brain barrier and infiltration of inflammatory neutrophils were also prevented. Conclusion: These findings suggest that ansamycin nanoparticles could be used to treat bacterial meningitis. It has been shown that ansamycin nanoparaticles can prevent the mice from E. coli-induced mortality, therefore enhancing their outcome
Keywords: Escherichia coli; Bacterial meningitis; Ansamycin; polymeric nanoparticles; Improved outcomes